In Junior High School Boys, a Comparison Of Hollow Sprint and Acceleration Sprint Methods on the Sprinter 100 Meters - Rian Akbari; Herli Pardilla; Zulfah Zulfah (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2022)
The purpose of the study. The purpose of this study was to describe the increase in extracurricular spint abilities of male students at SMP Negeri 03. The research method was this study using an experiment with a quasi-experimental type of research and the research pattern used in this study was a nonequivalent control group design. Materials and methods. This design involves two groups, namely the experimental group and the control group, and the time of the study was carried out in June 2021. The subjects of this research were 10 extracurricular students of SMP Negeri 03 Bangkinang, Kampar Regency. Results. The results of this study can be concluded that the results of the 100 meter sprint ability of male extracurricular students at SMP Negeri 03 Bangkinang Kampar Regency with an average sprint ability of 100 meters 0.933, thus it can be concluded that by using the hollow sprint method on acceleration can improve the ability to run 100 sprints. Conclusions. Based on the results of data analysis, description, testing of research results and discussion, conclusions can be drawn based on the results of calculations that have been carried out, a significant value of 1.080 1.054 is obtained. Thus, the hypothesis states that there is a significant difference between the hollow sprint and accelerating sprint exercises on the 100-meter running speed of male students of SMP Negeri 3 Bangkinang in the 2020/2021 academic year, which is acceptable.